508 Syngeneic Pair-wise Transcriptomic/Epigenomic Analysis of Sporadic Cushing's Adenomas and Adjacent Gland Reveals Novel Tumorigenic Pathways. (1st April 2022) - Asuzu, David; Alvarez, Reinier; Fletcher, Patrick; Mandal, Debjani; Chittiboina, Prashant
Abstract : INTRODUCTION: Sporadic pituitary adenomas are found in more than 10% of the general population and are mutationally bland. The normal human pituitary transcriptome is unknown, precluding syngeneic studies on Cushing's disease (CD) pathogenesis. METHODS: We surgically annotated adenomas and adjacent normal glands and performed single cell RNAseq (scRNAseq; 10X Genomics Chromium 3') on 28, 724 cells from 6 patients (3 CD and 3 non-CD). We performed bulk RNAseq (Illumina Nextseq) in 7 patients (5 CD and 2 non-CD) and DNA methylation analysis (Illumina Infinium MethylEPIC 850k) in 6 patients (3 CD and 3 non-CD). Transcriptomic/epigenomic data were analyzed using R packages and custom Python pipelines for pairwise differential expression analyses. RESULTS: We mapped the post-natal human pituitary gland at single cell resolution and identified canonical resident pituitary cell classes. Corticotrophs were abundant within CD adenomas but rare in the surrounding normal gland, with downregulated POMC expression consistent with repression in the hypercortisolemic state. CD corticotrophs overexpressed signature genes PCSK1, PPP1R17, EGLN, RSPO3 and PMAIP1 compared to surrounding tissues. This gene signature was specific for core adenomas and correlated with anatomic demarcation at the time of surgery. We confirmed overexpression of PCSK1, PPP1R17, RSPO3 and PMAIP1 by independent RNAseq. We identified hypomethylation at the promoters of PMAIP1, PPP1R17 and RSPO3 but not PCSK1 or EGLN1 in CD adenomas. CONCLUSION: We mapped the transcriptome of the adult human pituitary gland, identified novel signature genes for CD and highlighted DNA methylation as an epigenetic mechanism of transcriptional activation in a number of Cushing's adenoma signature genes. We provide novel, targetable mechanistic pathways for therapeutic intervention in Cushing's disease.